RELEVANSI ILMU PENGETAHUAN SOSIAL DI TENGAH ISU-ISU KONTEMPORER: DARI PERUBAHAN IKLIM HINGGA KONFLIK GLOBAL - Rivaldy, Rugary (Jurnal Muara Pendidikan, 2024)
The research aims to understand the relevance of studying social sciences in addressing current issues such as climate change and global conflicts like forced migration and group discrimination. The research uses the literature study method. Data collection is conducted by searching for and reading several books and articles related to social phenomena and current issues to be discussed. The knowledge obtained is then recorded and the relationships between them are sought, resulting in comprehensive research. Research results lead to the thought that social sciences have a crucial position and play an important role as an education that can change societal mindset and awareness. By studying social science thinkers, we can see that there are distinctive characteristics and patterns of a society. Additionally, we can identify and capture the problems existing within that society. Furthermore, studying social sciences provides the understanding that social life is dynamic. Social life is always experiencing movement and change. This is what makes social sciences relevant to study, as they encourage us to continuously observe and critically monitor everything happening within society. Further research is expected to develop the analysis to produce broader and more critical insights.